The Legalization of Abortion and Its Influence on Youth Sexual Behavior and the Catholic Church: A Case Study of Adamawa State - Umaru, Isaac John; Akem, Ingwu Joseph; Asare, Solomon O.; Danjuma, Tyem Lawal; Yeboah, Genevieve A.; Salman, Julius Ishaya; Umaru, Hauwa A.; Ahmed, Maryam Usman (Darul Yasin Al Sys, 2026)
Although debates on abortion reform have intensified in Nigeria, limited attention has been paid to how partial legalization shapes youth perspectives and sexual and reproductive behaviors within specific sociocultural and religious contexts. This study examines how the limited legalization of abortion influences youth attitudes and behaviors in Adamawa State, with particular attention to demographic, cultural, and institutional factors, as well as the Catholic Church’s response to these changes. A qualitative approach was employed through interviews with health workers, clergy, and youths aged 18–25 from urban and rural areas of Adamawa State. Supplementary data were obtained from community forums, church outreach programs, and health service records, and the data were analyzed thematically to identify patterns in attitudes, behaviors, and institutional responses. The findings indicate a marked urban–rural divide, with urban youths reporting higher sexual activity, greater contraceptive use, and stronger support for reproductive autonomy. The study also found that the Catholic Church’s moral campaigns have had limited influence, particularly among urban youths who perceive religious teachings as less relevant to contemporary realities. In contrast, health workers were viewed as more trusted sources of guidance, while peers and media played a substantial role in shaping youth behavior. The study concludes that the evolving legal and cultural landscape in Adamawa State reflects a broader generational shift toward autonomy and informed decision-making among youths. These findings contribute to understanding the changing relationship between legal reform, religious influence, and youth reproductive behavior, and suggest that more balanced strategies integrating moral guidance, comprehensive education, and supportive policies are needed to promote healthy youth development in a changing society.